A Portrait of the Woman in Mass Media in the Case of Femicide of a Student in Pandeglang Regency - Rohmawati, Sinta; Malik, Abdul; Putri, Liza Diniarizky (Universitas Bunda Mulia, 2024)
This research aims to criticize and justify the subject position, object position, and reader position placed in the news text of the female student femicide case in Pandeglang Regency in the Radar Banten report. This research uses the Sara Mills model of discourse analysis using a critical paradigm, through a qualitative approach. This research was conducted using purposive sampling. The results of this research are that female victims of femicide are positioned as objects of discrimination and the subject is the storyteller, namely Radar Banten. The subject position has the freedom to tell the event but also interpret the various actions that build up the event. The position of the reader in the news text is more directed towards male readers. There are two ways to position the reader, with the mediation aspect and the cultural code aspect. The representation of female victims of femicide in Pandeglang Regency in Radar Banten's reporting is influenced by patriarchal ideology. Women are considered a marginal group that experiences injustice because it weakens women's position. Women in this news are stereotyped and labeled as being weak, helpless, and wrong.